Conservative treatment of patients with periapical lesions associated with extraoral sinus tracts - Soares, Janir Alves; de Carvalho, Fabíola Bastos [UNESP]; Pappen, Fernanda Geraldes [UNESP]; Araújo, Gustavo Sivieri [UNESP]; Lima, Regina K. de Pontes [UNESP]; Rodrigues, Vivian M. Tellaroli [UNESP]; Leonardo, Renato de Toledo [UNESP] (Wiley, 2007)
This paper describes the clinical courses of three cases with extra-oral sinus tract formation, from diagnosis and treatment to short-term follow-up and evaluation. All teeth involved had periradicular radiolucent areas noted on radiographic examination and extra-oral sinus tracts appearing on the chin with exudation and unpleasant aesthetic appearance. The adopted treatment protocol included treating the sinus tract surface simultaneously with the root canal therapy. After root canal shaping using 5.25% sodium hypochlorite solution, calcium hydroxide-based pastes associated with different vehicles were inserted into the root canal for 4 months, and were changed monthly. All the sinus tracts healed in 7 to 10 days. The apical lesions were completely repaired in a maximum period of 24 months. The treatment adopted provided a complete healing of the periapical lesions in a short follow-up period. Surgical repair of the cutaneous sinus tract was therefore unnecessary. © 2007 The Authors. Journal compilation © 2007 Australian Society of Endodontology.
Keywords: Calcium hydroxide; Camphorated paramonochlorophenol; Cutaneous sinus; Endodontics; Periapical periodontitis; biomedical and dental materials; calcium hydroxide; hypochlorite sodium; adolescent; adult; case report; female; human; male; radiography; skin fistula; tooth fistula; tooth periapical disease; Adolescent; Adult; Calcium Hydroxide; Cutaneous Fistula; Dental Fistula; Female; Humans; Male; Periapical Abscess; Root Canal Irrigants; Sodium Hypochlorite